The causal relationship between perfectionism and negative affect: Two experimental studies. (January 2023) - Hummel, Julia; Cludius, Barbara; Woud, Marcella L.; Holdenrieder, Julia; Mende, Nina; Huber, Veronika; Limburg, Karina; Takano, Keisuke
Abstract: Perfectionistic concerns and negative affect have been found to be associated in clinical and non-clinical populations. However, evidence regarding the causality and direction of these associations is scarce. In two studies, we tested whether an experimental induction of perfectionistic concerns would increase levels of negative affect, and whether the induction of negative affect would increase perfectionistic concerns. In Study 1, an unselected student sample was tested; Study 2 included students scoring high on trait perfectionistic concerns, and both these samples either randomly received a perfectionistic-concerns induction or a negative affect induction. Across both studies, participants' levels of perfectionistic cognitions, perfectionistic interpretation bias, and negative affect were assessed before and after the corresponding induction. The perfectionistic-concerns induction only showed effects in participants high in perfectionistic concerns. Additionally, in Study 2, we found the expected effect of the perfectionistic-concerns induction on negative affect. The negative affect induction increased negative affect across both studies, but showed no effect on perfectionistic concerns. Our results give some indication that a unidirectional causal relationship from perfectionistic concerns to negative affect may exist in individuals with high levels of trait perfectionism. Limitations and further implications are discussed. Highlights: Perfectionistic concerns can be manipulated in high trait perfectionists. Perfectionistic concerns unidirectionally influence negative affect. Negative affect does not influence perfectionistic concerns. Perfectionism and negative affect may be reduced by a short intervention.